Aflatoxin G1 exposure altered the expression of BDNF and GFAP, histopathological of brain tissue, and oxidative stress factors in male rats - Toraj Zamir-Nasta; Ardeshir Abbasi; Seyran Kakebaraie; Arash Ahmadi; Mona Pazhouhi; Cyrus Jalili (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Aflatoxins are highly toxic compounds that can cause acute and chronic toxicity in humans and animals. This study aimed to evaluate the expression of BDNF and GFAP, histopathological changes, and oxidative stress factors in brain tissue exposed to aflatoxin G1 (AFG1) in male rats. Experimental approach: Twenty-eight male Wistar rats were used. Animals were randomly divided into 4 groups of 7 each. The control group received 0.2 mL of corn oil and the treatment groups were exposed to AFG1 (2 mg/kg) intra-peritoneally for 15, 28, and 45 days. The tissue was used for histopathological studies, and the level of TAC, SOD, and MDA, and the expression of BDNF and GFAP genes were evaluated. Findings/Results: Real-time PCR results showed that AFG1 increased GFAP expression and decreased BDNF expression in AFG1-treated groups compared to the control group. The tissue level of TAC and SOD over time in the groups receiving AFG1 significantly decreased and the tissue level of MDA increased compared to the control group. Histopathological results showed that AFG1 can cause cell necrosis, a reduction of the normal cells number in the hippocampal region of CA1, cerebral edema, shrinkage of nerve cells, formation of space around neuroglia, and diffusion of gliosis in the cerebral cortex after 45 days. Conclusion and implication: AFG1, by causing pathological complications in cortical tissue, was able to affect the exacerbation of nerve tissue damage and thus pave the way for future neurological diseases.